El Excentrico, 1980-12-01 - Garcia, Bert:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2024)
December 1980 [Diciembre de 1980]. Ano 31, No. 8. Cover contains a portrait of the former Santa Clara County District Attorney, Joseph F. Mayen. The headline reads, "La Ley y Usted" (transl: The Law and You).